2007
DOI: 10.1111/j.1365-2125.2007.02926.x
|View full text |Cite
|
Sign up to set email alerts
|

A pharmacokinetic model for L‐carnitine in patients receiving haemodialysis

Abstract: What is already known about this subject • Carnitine is essential for fatty acid metabolism, and is obtained from the diet and endogenous synthesis. • Patients with renal failure who are on chronic haemodialysis may require carnitine supplementation. • It is known that carnitine depletion in these patients may take years to develop, and that measurements of plasma carnitine may not be predictive of loss of carnitine from muscle, the main pool of carnitine in the body. What this study adds • This paper adds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…Previous studies have shown that plasma L-carnitine level was decreased in patients with antiretroviral toxic neuropathy, and oral L-carnitine supplementation seems to result in plasma levels that are higher than in healthy individuals [16,17]. So, the recommended dose for patients need to be further studied due to the close relationship between the endogenous L-carnitine level and pathological state.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that plasma L-carnitine level was decreased in patients with antiretroviral toxic neuropathy, and oral L-carnitine supplementation seems to result in plasma levels that are higher than in healthy individuals [16,17]. So, the recommended dose for patients need to be further studied due to the close relationship between the endogenous L-carnitine level and pathological state.…”
Section: Discussionmentioning
confidence: 99%
“…Undoubtedly, L-carnitine is effective for the treatment of inherited disorders related to functional anomalies in a specific organic cation/carnitine transporter (OCTN2), in drug-induced Lcarnitine deficiency and in cases of excessive excretion of L-carnitine because of renal tubular disorders and in patients on haemodialysis (Angelini et al, 2006;Fornasini et al, 2007;Lheureux et al, 2005). The safety profile of L-carnitine allows its frequent use in cocktails of food additives that are aimed to increase the oxidation of FA to eliminate body fat and thus produce cosmetic effects.…”
Section: Effects Of L-carnitine Supplementationmentioning
confidence: 99%
“…Secondary L-carnitine deficiency occurs due to genetically defined disturbances in fatty acid oxidation and amino acid homeostasis. Several medical conditions, such as cirrhosis and other metabolic disorders, lead to secondary L-carnitine deficiency, as well as hemodialysis or kidney failure (Fornasini et al, 2007, Virmani & Binienda, 2004. Both disorders induce the same symptoms, like periodic encephalopathies which often come along with www.intechopen.com hypoglycemia and hypoketonia.…”
Section: L-cartinine In the Cnsmentioning
confidence: 99%